2003
DOI: 10.1007/s10227-002-0114-5
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Tolerability of Clobetasol Propionate Foam 0.05% in the Treatment of Mild to Moderate Plaque-type Psoriasis of Nonscalp Regions

Abstract: Clobetasol propionate foam 0.05% is safe and effective for the treatment of plaque-type psoriasis on scalp and nonscalp areas, when applied twice daily for two weeks. As it is understood that patient dissatisfaction with select topical formulations affects their compliance with therapy, which necessarily affects the effectiveness of the therapy, the results of the patient's poststudy questionnaire suggest that there are multiple and integrated benefits for the use of clobetasol foam in the treatment of psorias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 14 publications
0
34
0
7
Order By: Relevance
“…In a randomized, double-blind, placebo-controlled evaluation of clobetasol propionate foam that enrolled 279 patients with scalp psoriasis, patient and physician global assessment scores improved significantly after 2 weeks (both P < 0.0001). 31 This result is supported by the findings of a randomized, single-blind comparison between clobetasol propionate foam 0.05% and clobetasol propionate solution 0.05% in 32 patients with scalp psoriasis. The study concluded that after 2 weeks, a significantly greater absolute reduction in psoriasis severity was seen in the group using the foam (P ¼ 0.03).…”
Section: Current Treatments For Scalp Psoriasismentioning
confidence: 58%
See 3 more Smart Citations
“…In a randomized, double-blind, placebo-controlled evaluation of clobetasol propionate foam that enrolled 279 patients with scalp psoriasis, patient and physician global assessment scores improved significantly after 2 weeks (both P < 0.0001). 31 This result is supported by the findings of a randomized, single-blind comparison between clobetasol propionate foam 0.05% and clobetasol propionate solution 0.05% in 32 patients with scalp psoriasis. The study concluded that after 2 weeks, a significantly greater absolute reduction in psoriasis severity was seen in the group using the foam (P ¼ 0.03).…”
Section: Current Treatments For Scalp Psoriasismentioning
confidence: 58%
“…48 In a randomized, double-blind, placebo-controlled evaluation of clobetasol propionate foam 0.05%, patients ranked the foam as superior to other topical medications they had received, based on a quality-of-life assessment. 31 In a randomized comparison, patients spent significantly less time applying a foam-based corticosteroid treatment medication than they did applying their previous topical medications (P < 0.001); a similar trend was not observed for patients applying cream or solution-based corticosteroid treatment. 23 Similarly, a comparison of betamethasone valerate foam 0.12% with other corticosteroid or calcipotriol formulations found that the foam was considered easier and more convenient (P < 0.01).…”
Section: Safetymentioning
confidence: 77%
See 2 more Smart Citations
“…субпопуляций) в патогенезе заболевания подтверж-дается участием их в формировании псориатическо-го инфильтрата. Оценка состояния иммунной си-стемы позволяет наиболее информативно охаракте-ризовать стадии активности патологического про-цесса при псориазе, типы его течения и определить наиболее эффективные методы терапии [2][3][4][5][6][7].…”
Section: ключевые слова: карталин псориаз лечение липиды иммуногиunclassified